Identifiable Risk Factors for Lymph Node Metastases in Grade 1 Endometrial Carcinoma. Issue 8 (October 2017) - Pavlakis, Kitty; Rodolakis, Alexandros; Vagios, Stylianos; Voulgaris, Zannis; Messini, Irini; Yiannou, Petros; Vlachos, Athanasios; Panoskaltsis, Theodoros
Abstract : Objective: The aim of this study was to evaluate the clinicopathological features related to lymph node metastases in grade 1 endometrial carcinomas. Materials and Methods: Five hundred ninety-nine cases of endometrial carcinoma treated with total hysterectomy bilateral salpingo-oophorectomy and pelvic lyphadenectomy between 2001 and 2015 were retrieved from the pathology files of IASO Women's Hospital, Athens, Greece. Of these, 345 were grade 1 endometrioid carcinomas and were included in the study. Features such as the age of the patients, the stage, the location, and size of the tumors, as well as the existence of microcystic, elongated, and fragmented pattern invasion or lymph vascular space invasion, were estimated. Results: In our cohort of endometrial carcinomas, features related to an increased risk of lymph node metastases were stages IB or higher; the location of the tumor in the lower uterine segment; the identification of microcystic, elongated, and fragmented pattern of invasion; and the existence of lymph vascular emboli. When considering the size of the tumors, only stage IA myoinvasive cancers of larger than 4 cm in diameter were significantly associated with nodal disease. In addition, a statistically significant relationship was found between the number of excised lymph nodes and the possibility to detect nodal disease. Conclusions: Full surgical staging carries a substantial risk of operative complications, and, indeed, it can be avoided in most cases of grade 1 endometrial carcinomas. Nevertheless, even in the low-risk group of patients, there are clinicopathological parameters that should alert the clinician for the possibility of a more disseminated disease.